2020
DOI: 10.5334/tismir.39
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Popularity and Temporal Drift of Music Genre Preferences

Abstract: In this paper, we address the problem of modeling and predicting the music genre preferences of users. We introduce a novel user modeling approach, BLL u , which takes into account the popularity of music genres as well as temporal drifts of user listening behavior. To model these two factors, BLL u adopts a psychological model that describes how humans access information in their memory. We evaluate our approach on a standard dataset of Last.fm listening histories, which contains fine-grained music genre info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…The presented approach helps add music from the long-tail into the recommendation list. In our previous research [41,42], we have used a framework [43] that employs insights from human memory theory to design a music recommendation algorithm that provides more accurate recommendations than collaborative filtering-based approaches for three groups of users, i.e., low-mainstream, mediummainstream and high-mainstream users. While the awareness of popularity bias in music recommender systems increases (e.g., [44]), the characteristics of music consumers whose preferences lie beyond popular, mainstream music are still not well understood.…”
Section: Long-tail Recommendationsmentioning
confidence: 99%
“…The presented approach helps add music from the long-tail into the recommendation list. In our previous research [41,42], we have used a framework [43] that employs insights from human memory theory to design a music recommendation algorithm that provides more accurate recommendations than collaborative filtering-based approaches for three groups of users, i.e., low-mainstream, mediummainstream and high-mainstream users. While the awareness of popularity bias in music recommender systems increases (e.g., [44]), the characteristics of music consumers whose preferences lie beyond popular, mainstream music are still not well understood.…”
Section: Long-tail Recommendationsmentioning
confidence: 99%
“…We focuse on popularity bias, a well-studied form of bias in recommender systems research. This form of bias refers to the underrepresentation of less popular items in the produced recommendations and can lead to a significantly worse recommendation quality for consumers of long tail or niche items [3,10,12,13]. Abdollahpouri et al [3] show that state-of-the-art movie recommendation algorithms suffer from popularity bias, and introduce the delta-GAP metric to quantify the level of underrepresentation.…”
Section: Related Workmentioning
confidence: 99%
“…Algorithm Configurations. To configure the decay parameter of the Base-level component and in line with previous studies [12], we analyze the relistening behavior using a log-log plot as shown in Figure 1. We observe a good fit for a power law distribution of relistening behavior, i.e., linear fit in the log-log space.…”
Section: Relistening Behaviormentioning
confidence: 99%
“…The declarative memory module of ACT-R stores and retrieves information and consists of separate components. In contrast to prior work, which uses the base-level component to model predict user preferences in various domains (e.g., [9][10][11][12]14]), we investigate the utility of five components, i.e., (i) base-level, (ii) spreading, (iii) partial matching, (iv) valuation, and (v) noise component, in a next track prediction scenario. These components enable us to investigate the effect of various factors on track relistening behavior, i.e., (i) recency and frequency of prior exposure to tracks, (ii) co-occurrence of tracks, (iii) the similarity between tracks, (iv) familiarity with tracks, and (v) randomness in behavior.…”
mentioning
confidence: 99%